Tourism growth and investment in Bali’s inclusive economic recovery in 2023: A spatial and econometric approach - Tantra, I Gusti Lanang Putu; Murthi, Ngurah Wisnu (Privietlab, 2025)
This study investigates the relationship between tourism development, total realized investment, and inclusive growth in Bali during the 2023 economic recovery period. The primary objective is to analyze how international and domestic tourist visits, along with investment inflows, influence inclusive growth across Bali’s regions. This study employs various econometric models, including linear trend analysis, multiple regression, and a spatial lag model (SAR) to capture the spatial dependencies between regions. Using data on tourist visits, realized investments, ICT use, labor force participation, and real per capita expenditure, this study builds an Inclusive Growth Index (IGI) for Bali. The results indicate that tourism and investment significantly contribute to inclusive growth, and spatial factors also play a critical role in determining regional disparities in growth. The findings have important policy implications for promoting sustainable tourism and investment strategies to ensure equitable and inclusive development across Bali.